A role for interleukin-1β in synaptic function - Vereker, Emily (Trinity College (Dublin, Ireland). Department of Physiology, 2001)
The proinflammatory cytokine, interleukin-1β (IL -1β ). one of the most extensively studied cytokines to date, is known to play a pivotal role in neurodegenerative, inflammatory and infectious diseases. Moreover, IL-1β has been implicated in the impairment of long-term potentiation (LTP), a model for learning and memory, and at least one biochemical correlate associated with LTP, i.e., glutamate release. The mechanisms underlying the impairment of LTP in deleterious circumstances, such as in ageing, remains to be fully elucidated. The focus of this study involved investigating the possibility that the stress-activated protein kinases, JNK and p38, underlie this impairment and that activation is initiated by an increase in IL -1β concentration and reactive oxygen species (ROS) formation.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin